1986
DOI: 10.1111/j.1432-1033.1986.tb09829.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of casein kinase‐2 from Saccharomyces cerevisiae

Abstract: A type-2 casein kinase (YCK-2), lacking the 25-kDa autophosphorylatable /3 subunit characteristic of animal casein kinases-2, has been obtained in a nearly pure form from Saccharomyces cerevisiae and was compared with liver casein kinase-2 (LCK-2). A 22-kDa phosphorylatable protein, copurifying with YCK-2, can be removed by ultracentrifugation at low ionic strength and is shown by several criteria to be unrelated to the / 3 subunit of LCK-2. The native M , of YCK-2, deprived of the 22-kDa phosphoprotein, is ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…At 200 mM K+ or Na+, activity was inhibited by more than 90%. This property is also shared by CK I1 from yeast (Meggio et al, 1986).…”
Section: Lonic Requirements For Activitymentioning
confidence: 88%
“…At 200 mM K+ or Na+, activity was inhibited by more than 90%. This property is also shared by CK I1 from yeast (Meggio et al, 1986).…”
Section: Lonic Requirements For Activitymentioning
confidence: 88%
“…262: , 1987 Casein kinase II is a cyclic-nucleotide-independent protein kinase which phosphorylates a broad spectrum of both cytoplasmic and nuclear substrates (for a review, see reference 10). The enzyme is widely distributed among eucaryotic organisms and has been purified from a number of mammalian and avian species (10), Drosophila melanogaster (8), and Saccharomyces cerevisiae (19,22 (12,26), and in some systems two related alphalike polypeptides, alpha and alpha', have been observed (4, 10). The beta subunit becomes phosphorylated when the enzyme is allowed to undergo autophosphorylation, but the function of this subunit and the significance of autophosphorylation are poorly understood.…”
mentioning
confidence: 99%
“…By synthesis of large polypeptides with different amino acid mixtures and different charge distributions, it may be possible to evaluate quantitatively the contributing components. PK-P has some properties in common with yeast casein kinase II (8,9), such as sensitivity to acidic polysaccharides and activation by basic compounds. However, whereas casein kinase II was isolated from a soluble yeast extract and did not require a detergent for stability, we isolated PK-P by extraction of yeast membranes with Triton X-100 and showed that the detergent was required for stability of the enzyme (6).…”
Section: Discussionmentioning
confidence: 99%
“…10-(3-Aminopropyl)-2-chlorophenothiazine was supplied by Smith Kline & French. Casein kinase II from yeast and skeletal muscle was prepared through the phosphocellulose column step as described (8,9). PK-C was prepared as described (10).…”
Section: Methodsmentioning
confidence: 99%